Antimicrobial susceptibility profiles and tentative epidemiological cutoff values of Legionella pneumophila from environmental water and soil sources in China - Yang, Jin-Lei; Sun, Honghua; Zhou, Xuefu; Yang, Mo; Zhan, Xiao-Yong (Frontiers in Microbiology, 2022)
Legionnaires’ disease (LD), caused by Legionella, including the most prevalent Legionella pneumophila, has been treated primarily with antibiotics. Environmental water and soil are the reservoirs for L. pneumophila. Studying antimicrobial susceptibility using a large number of isolates from various environmental sources and regions could provide an unbiased result. In the present study, antimicrobial susceptibility of 1464 environmental L. pneumophila isolates that were derived from various environmental water and soil sources of 12 cities in China to rifampin (RIF), erythromycin (ERY), clarithromycin (CLA), azithromycin (AZI), ciprofloxacin (CIP), moxifloxacin (MOX), levofloxacin (LEV), and doxycycline (DOX) was investigated, and minimum inhibitory concentration (MIC) data were obtained. We show that regarding macrolides, ERY was least active (MIC90 = 0.5 mg/L), while CLA was most active (MIC90 = 0.063 mg/L). A total of three fluoroquinolones have similar MICs on L. pneumophila. Among these antimicrobials, RIF was the most active agent, while DOX was the most inactive one. We observed different susceptibility profiles between serogroup 1 (sg1) and sg2-15 or between water and soil isolates from different regions. The ECOFFs were ERY and AZI (0.5 mg/L), RIF (0.002 mg/L), CIP, CLA and MOX (0.125 mg/L), LEV (0.063 mg/), and DOX (32 mg/L). Overall, two fluoroquinolone-resistant environmental isolates (0.14%) were first documented based on the wild-type MIC distribution. Not all azithromycin-resistant isolates (44/46, 95.65%) harbored the lpeAB efflux pump. The MICs of the ERY and CLA on the lpeAB + isolates were not elevated. These results suggested that the lpeAB efflux pump might be only responsible for AZI resistance, and undiscovered AZI-specific resistant mechanisms exist in L. pneumophila. Based on the big MIC data obtained in the present study, the same defense strategies, particularly against both CLA and RIF, may exist in L. pneumophila. The results determined in our study will guide further research on antimicrobial resistance mechanisms of L. pneumophila and could be used as a reference for setting clinical breakpoints and discovering antimicrobial-resistant isolates in the clinic, contributing to the antibiotic choice in the treatment of LD.